Core–Shell Heterojunction of Silicon Nanowire Arrays and Carbon Quantum Dots for Photovoltaic Devices and Self-Driven Photodetectors - Xie, Chao; Nie, Biao; Zeng, Longhui; Liang, Feng-Xia; Wang, Ming-Zheng; Luo, Linbao; Feng, Mei; Yu, Yongqiang; Wu, Chun-Yan; Wu, Yucheng; Yu, Shu-Hong (ACS nano, 2014)
Silicon nanostructure-based solar cells have lately intrigued intensive interest because of their promising potential in next-generation solar energy conversion devices. Herein, we report a silicon nanowire (SiNW) array/carbon quantum dot (CQD) core–shell heterojunction photovoltaic device by directly coating Ag-assisted chemical-etched SiNW arrays with CQDs. The heterojunction with a barrier height of 0.75 eV exhibited excellent rectifying behavior with a rectification ratio of 103 at ±0.8 V in the dark and power conversion efficiency (PCE) as high as 9.10% under AM 1.5G irradiation. It is believed that such a high PCE comes from the improved optical absorption as well as the optimized carrier transfer and collection capability. Furthermore, the heterojunction could function as a high-performance self-driven visible light photodetector operating in a wide switching wavelength with good stability, high sensitivity, and fast response speed. It is expected that the present SiNW array/CQD core–shell heterojunction device could find potential applications in future high-performance optoelectronic devices.